Taxonomic review of the leafhopper genus Stirellus Osborn & Ball (Hemiptera: Cicadellidae: Deltocephalinae: Stenometopiini) from Pakistan with description of a new species - Shah, Bismillah; Naveed, Hassan; Duan, Yani (Zootaxa, 2020)
The leafhopper genus Stirellus Osborn & Ball is revised from Pakistan with the description and illustrations of a new species Stirellus mankiensis Shah & Duan sp. n. and a new record Stirellus tolla n. rec. to Pakistan. A checklist and key for the known species of Stirellus from Pakistan are also given in the present study.